Mental health and primary care: an experience with community health agents in Salvador-BA - Noêmia Aragão Casais; Miriam dos Santos Alves; Mariane Marques de Souza Santos; Ana Carolina Moreira Oliveira; Allann da Cunha Carneiro; Josenaide Engracia dos Santos (Universidade de Fortaleza, 2009)
Objective: To share an experience of a link between primary care and mental health by means of matrix support. Method: A survey conducted from March to December 2007, in Pernambués neighborhood, District of Cabula-beiru, in Salvador - Bahia. The shared knowledge construction was carried out by residents of the Multidisciplinary Residency Program in Health from the Nucleus of Mental Health, State University of Bahia, with Community Health Agents (ACS). Meetings, discussions and domiciliary visits were applyed as sharing technics and tools with phonographic recording, photographic register and report. The obtained information were evaluated regarding their content and were divided into stages and categories. Results: We determined the following stages by means of the technique: approach, ties' strengthening, teamwork and conclusion. The results were analyzed based on the ACS' everyday interactivity for cooperation, thus obtaining the development of a critical spirit in the assesment of the relationship between primary care and mental health. Final Considerations: The exchange of experiences produced significant learning, besides health promotion for all those involved in the process: ACS, families cared for and residents.